2015
DOI: 10.1186/s13075-015-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of NLRP3 inflammasome in peripheral blood cells of patients with active rheumatoid arthritis

Abstract: IntroductionInterleukin-1β (IL-1β) is a major inflammatory cytokine, produced predominantly by innate immune cells through NLRP3-inflammasome activation. Both intrinsic and extrinsic danger signals may activate NLRP3. Genetic variations in NLRP3-inflammasome components have been reported to influence rheumatoid arthritis (RA) susceptibility and severity. We sought to assess the activity of NLRP3-inflammasome in patients with active RA compared to healthy individuals.MethodIntracellular protein expression of NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 48 publications
2
96
0
1
Order By: Relevance
“…Inflammasome activation TLR-4 stimulation with lipopolysaccharide (LPS, Escherichia coli O111; Merck) (250 pg·mL −1 , incubated for 2 h at a 37°C/5% CO 2 humidified incubator) was followed by NLRP3 inflammasome activation with a 5 mM ATP pulse (ATP disodium salt hydrate; Sigma-Aldrich) for 20 min at 37°C/5% CO 2 , in the presence or absence of caspase-1 inhibitor (Calbiochem) (online supplementary figure S1), as previously described [24]. Cells were harvested by centrifugation at 1500×g at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammasome activation TLR-4 stimulation with lipopolysaccharide (LPS, Escherichia coli O111; Merck) (250 pg·mL −1 , incubated for 2 h at a 37°C/5% CO 2 humidified incubator) was followed by NLRP3 inflammasome activation with a 5 mM ATP pulse (ATP disodium salt hydrate; Sigma-Aldrich) for 20 min at 37°C/5% CO 2 , in the presence or absence of caspase-1 inhibitor (Calbiochem) (online supplementary figure S1), as previously described [24]. Cells were harvested by centrifugation at 1500×g at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] In addition, previous studies showed that the NLRP3 inflammasome complex and cytokines IL-1b and IL-18 play essential roles in the development of T2DM and its major complica- . Data represent means 6 SD.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting NALP3 or downstream caspases may be of benefit in suppressing IL-1b production in RA. 126 Other investigators demonstrated that A20, an RA susceptibility gene, puts a break in NALP3 and reduces inflammasome activation. 125 Likewise, excessive NALP3 inflammasome activation drives arthritis in A20 knockout mice, suggesting that A20 mutant mice might be a suitable preclinical model for validating the effectiveness of experimental therapies for RA-targeting inflammasomes, IL-1 signalling, or both.…”
mentioning
confidence: 99%